Pengembangan Booklet Materi Hubungan Antar Makhluk Hidup dalam Ekosistem dengan Penguatan Karakter Mandiri Siswa Sekolah Dasar - Alvi Nanda Choirina; Bintartik, Lilik; Utama, Candra (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2023)
Various problems arise in Natural Science learning in elementary school. One of them is not using teaching materials other than thematic package books and worksheet companion books. LKS books students purchase are printed in black and white on opaque paper. The material presented is still limited, particularly in relationships between living things in ecosystems. Practice questions are also limited, so the teacher has to provide additional questions. In addition, only a tiny proportion of students are independent. The rest still depend on the teacher and other students when given assignments or asked to work on problems. So, teaching materials must be presented to support learning activities with variations that interest students in practicality because the size is relatively small and can strengthen students' independent character. One type of teaching material that is suitable to be developed is a booklet. This research aims to develop booklets that are practical, valid, effective and can strengthen independent character. The type of research used is the ADDIE model development research, composed of 5 steps: analyze, design, develop, implement and evaluate. Research data was obtained from teaching materials experts, material experts, teachers, and students at SDN Karangsari 2 Kota Blitar, with a total of 27 students. Data collection uses interviews, observations, documentary studies, questionnaires, and written tests. Booklet validation results data achieve very valid criteria where the average is 94.5%. The average practicality test results by students and teachers were 98.31% very practical. The effectiveness of booklets reached 77.47%, and the percentage of student independence reached 94.06%. After testing the booklet on students, a positive response was obtained; learning became more fun, exciting, and easy to understand. The booklet on the relationship between living things in ecosystems is very valid, convenient and effective, so they are suitable for use in learning.